2019
DOI: 10.3390/ijms20236021
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Functions of B Cells in the Pathogenesis of Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by excessive autoantibody production and multi-organ involvement. Although the etiology of SLE still remains unclear, recent studies have characterized several pathogenic B cell subsets and regulatory B cell subsets involved in the pathogenesis of SLE. Among pathogenic B cell subsets, age-associated B cells (ABCs) are a newly identified subset of autoreactive B cells with T-bet-dependent transcriptional programs and unique functional fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 167 publications
4
49
0
1
Order By: Relevance
“…As outlined earlier, the fundamental importance of distributed BCR and TCR signaling pathways in SLE pathogenesis has been well established via both clinical and experimental evidence [51,52]. In this context, we also observed defects in several genes involved in these signaling pathways ( Figures 5B and 6B).…”
Section: Discussionsupporting
confidence: 78%
“…As outlined earlier, the fundamental importance of distributed BCR and TCR signaling pathways in SLE pathogenesis has been well established via both clinical and experimental evidence [51,52]. In this context, we also observed defects in several genes involved in these signaling pathways ( Figures 5B and 6B).…”
Section: Discussionsupporting
confidence: 78%
“…[52] In a recent study, the FCGR2A polymorphisms have been linked to SLE susceptibility in Mexican patients [46]. As outlined earlier, the fundamental importance of BCR and TCR signaling pathways in SLE pathogenesis has been well established via both clinical and experimental evidence [53][54][55]. In the TCR signaling pathway, we observed lower expression of several genes like CBLB, PPP3CC, NFKB1, CD3E, and ZAP70.…”
Section: Discussionsupporting
confidence: 52%
“…Patients with SLE usually present blood circulating antinuclear antibodies, which result in immune complex deposition and complement consumption in multiple organs, leading to cytopenia, glomerulonephritis, rash, and serositis. Accordingly, antinuclear antibodies are crucial for the progression of SLE 39 . Many studies have shown that the imbalance of Treg and Th17 responses is crucial for the pathogenesis of SLE 40‐42 …”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Accordingly, antinuclear antibodies are crucial for the progression of SLE. 39 Many studies have shown that the imbalance of Treg and Th17 responses is crucial for the pathogenesis of SLE. [40][41][42] Th17 cells can induce vascular inflammation by increasing the secretion of IL-17A during the pathogenesis of SLE.…”
Section: Sys Temi C Lupus Ery Thematosusmentioning
confidence: 99%